Involvement of Cytochrome P450 in Organic-Solvent Tolerant Bacillus subtilis GRSW1-B1 in Vanillin Production via Ferulic Acid Metabolism - Panaya Kotchaplai; Jedsadakorn Ninrat; Gumpanat Mahipant; Alisa S. Vangnai (Fermentation, 2022)
The detection of vanillin during the metabolism of ferulic acid by several Bacillus strains has been reported; however, its occurrence is not yet understood. Herein, the potential enzymes involved in vanillin production during ferulic acid metabolism in the previously reported butanol-tolerant Bacillus subtilis strain GRSW1-B1 were explored. The recombinant E. coli cells that overexpressed phenolic acid decarboxylase (PadC) rapidly converted ferulic acid to 4-vinylguaiacol. The detection of vanillin was concurrent with a decrease in 4-vinylguaiacol. In addition, the reversible abiotic conversion of 4-vinylguaiacol and apocynol was observed. The overexpression of CypD, a Bacillus P450, resulted in notable production of vanillin. The two-step conversion of ferulic acid yielded 145 μM over 72 h at pH 9. Vanillin yields of approximately 258 μM and 212 μM were obtained from ferulic acid metabolism by recombinant E. coli coexpressing PadC and CypD after conversion for 72 h, at pH 9 and 10, respectively. Several possibilities that underlie the production of vanillin were discussed. This information is useful for understanding ferulic acid metabolism by Bacillus strains and for further improving this strain as a host for the production of valuable compounds from biomass.